2022
DOI: 10.1371/journal.pone.0277413
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic comparison of COVID-19 outpatients and inpatients treated with Remdesivr: A retrospective cohort study

Abstract: Introduction Since the late COVID-19, many countries have faced various surges and peaks within the number of infected. Iran was one of the countries that faced many surges and peaks within these years and faced many inadequacies and shortages of resources and hospital beds. Hence the healthcare system started using in-hospital medication such as Remdesivir in outpatients to reduce the load of patients admitted to the hospital. This study aimed to evaluate and compare the reported signs, symptoms, and outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Drug shortages (i.e., remdesivir) during the pandemic affected treatment options for our patients [ 41 ]. This in combination with continuous changes in national treatment protocol over the LOS may also have affected our data.…”
Section: Discussionmentioning
confidence: 99%
“…Drug shortages (i.e., remdesivir) during the pandemic affected treatment options for our patients [ 41 ]. This in combination with continuous changes in national treatment protocol over the LOS may also have affected our data.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of timely treatment and studies showing similar clinical outcomes in outpatients underline the need for early COVID-19 diagnosis while expanding access to outpatient antimicrobial treatment facilities. Several studies showed that RDV infusion in the outpatient setting seems to be a safe and efficient alternative to conventional hospitalization for treating non-severe COVID-19 patients [ 100 ]. In one of the studies, only 2% reported adverse effects and only 5% required hospitalization [ 101 ].…”
Section: Expert Opinion and Future Directionsmentioning
confidence: 99%